The garden of promises and lies - Brackston, Paula (Brackston, Paula. Found things., 2020)
"The third installment of a bewitching series "brimming with charm and charisma" that will make "fans of Outlander rejoice!" (Woman's World Magazine). New York Times bestselling author Paula Brackston's second novel in the Found Things series, Secrets of the Chocolate House, was called a "time-swapping romance [that] will please fans of Alice Hoffman" (Publishers Weekly). Now, Brackston returns to the Found Things series with a third book, The Garden of Promises and Lies. As the bustle of the winter holidays in the Little Shop of Found Things gives way to spring, Xanthe is left to reflect on the strange events of the past year. While she's tried to keep her time-traveling talents a secret from those close to her, she is forced to take responsibility for having inadvertently transported the dangerous Benedict Fairfax to her own time. Xanthe comes to see that she must use her skills as a spinner if she and Flora are ever to be safe, and turns to the Spinners book for help. It is then that a beautiful antique wedding dress sings to her. Realizing the dress and her adversary are connected in some way, she answers the call. She finds herself in Bradford-on-Avon in 1815, as if she has stepped into a Jane Austen story. Now in Xanthe's time, Fairfax is threatening Xanthe into helping him with his evil doings, and demonstrates all too clearly how much damage he is capable of causing. With Fairfax growing ever more powerful, Xanthe enlists the help of her boyfriend Liam, taking him back in time with her. It is a decision that might just ensure she prevails over her foe, but only by putting her life-and his-on the line"--